Strategies and Model for Empowering Indigenous Peoples and Local Communities in Encouraging Tourism Sector Performance - Mochamad, Ulum Chazienul; Matthoriq, Matthoriq; Wicaksono, Aries Samudra (JPAP: Jurnal Penelitian Administrasi Publik, 2025)
Tourism can empower communities by providing opportunities for increased income, and skill and participation development. The purpose of this paper is to describe empowerment strategies and model that can be adopted to encourage the performance of the tourism sector. This also applies to indigenous peoples and local communities in Papua. This strategy can be realized through four steps: First, socializing the role of the community as a subject, both as the main actor and/or taking part with active participation. Second, utilizing a more democratic development implementation mechanism through the principles of governance and community participation. Third, mobilizing human resources. Finally, maximizing the role of the government in facilitating, regulating and providing assistance to ensure a conducive and sustainable tourism business and investment climate.